Effects of LO-phonon confinement on electron mobility in GaAs-Al₀.₄₅ Ga₀.₅₅As superlattice - Abouelaoualim, D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The parallel and perpendicular electron mobilities in a GaAs-Al₀.₄₅ Ga₀.₅₅As superlattice have been calculated. The scattering of electrons by confined longitudinal optical phonons was taken into account. Using the quantum treatment, we offered the new wavefunction of electron miniband conduction in the superlattice as well as reformulation of the slab model for confined LO-phonon modes. An expression for the relaxation time was obtained. Our results show that the relaxation time depends significantly on the total energy of electrons. The effect of the band nonparabolicity on the relaxation time was analyzed. At 300 K, the calculated results reveal that the electron mobility is enhanced when the well width in the superlattice is equal to 45 A.